Treatment of Elderly Patients with Acute Symptomatic OVCF: A Study of Comparison of Conservative Treatment and Percutaneous Kyphoplasty - Yu, Dejun; Liu, Zuyao; Wang, Hongqing; Yao, Ran; Li, Fu; Yang, Yang; Sun, Fenglong (Frontiers in Surgery, 2022)
Objective: To study the comparison of conservative treatment and percutaneous kyphoplasty in elderly patients with acute symptomatic osteoporotic vertebral compression fracture (OVCF). Methods: 30 elderly patients with acute symptomatic OVCF in Con group received conservative treatment, while 30 patients in PKP group received percutaneous kyphoplasty treatment. To compare the visual analog scale (VAS), dallas pain questionnaire, vertebral body leading edge height, the cobb angle of injured vertebrae, the MOS item short from health survey (SF-36), Barthel index and mimi-mental state examination (MMSE) of patients post-treatment in these two groups. Results: At 3 days, 3 months and 6 months post-treatment, the score of VAS and the cobb angle of injured vertebrae in patients of PKP group are all significantly lower than those in Con group (P<0.05), while the height of vertebral body leading edge in patients of PKP group is significantly higher than that in Con group (P<0.05). At 6 months post-treatment, the scores of the four dimensions of the dallas pain questionnaire scale in PKP group were all significantly lower than those in the Con group (P<0.05), while the score of SF-36 (PCS), SF-36 (MCS) and Barthel in patients of PKP group were all significantly lower than those in Con group (P<0.05), and there was no significantly different in the score of MMSE between these two group (P>0.05). Conclusion: Compared with conservative treatment, PKP treatment of olderly patients with acute symptomatic OVCF provides rapid pain relief, restoration of damaged vertebral body height and correction of Cobb's angle, and improved quality of life.